Preparation process of hollow fiber fabric with heat preservation, dryness and moisture absorption functions

By spinning with polyester, polylactic acid and polyester masterbatches and washing, alkaline washing and modification and finishing, hollow fiber fabrics with improved moisture absorption and warmth performance were prepared, solving the warmth and moisture absorption performance of existing fabrics. The shortcomings.

CN119411254APending Publication Date: 2025-02-11YIWU ZHISHANG SOCKS
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411430011.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing fabrics have shortcomings in terms of warm and moisture absorption performance. High-density fabrics have good moisture permeability but poor water resistance, coated fabrics have good water resistance but poor moisture permeability, and the lack of capillary effect of hollow fibers leads to unsatisfactory moisture absorption, dryness and warmth.

Method used

Polyester, polylactic acid and polyester masterbatches are used as spinning raw materials to obtain hollow fibers through hollow melt spinning, and the fiber wall integrity is destroyed by water washing and alkali washing processes, and impregnation and modification treatment is carried out in combination with the modification finishing solution to enhance the Water absorption and storage properties of fibers.

Benefits of technology

It improves the moisture absorption and warmth of the fabric while maintaining dryness, solving the shortcomings of traditional fabrics in terms of warmth and moisture absorption properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of hollow fiber preparation processes, in particular to a preparation process of a hollow fiber fabric with heat preservation, dryness and moisture absorption functions. The process comprises the following steps: firstly, selecting polyester, polylactic acid and polyester master batch as spinning raw materials, carrying out melt mixing, and carrying out hollow melt spinning by adopting a hollow fiber spinning plate to obtain hollow fibers; then, the hollow fiber obtained through spinning is made into yarn, and after the water washing or alkali washing process is conducted, the hollow fiber fabric is obtained through the weaving process; finally, the hollow fiber fabric is subjected to dipping modification treatment with the modification finishing liquid, and the hollow fiber fabric with the heat preservation, dryness and moisture absorption functions is obtained. Polyester and a small amount of polylactic acid are blended and then spun to obtain the hollow fiber, polyester master batches are added into the hollow fiber at the same time, the fiber wall of the hollow fiber can be damaged through subsequent water washing and alkali washing processes by means of addition of the master batches and the effect of the polylactic acid, moisture absorption is facilitated, and therefore the moisture absorption effect is improved; the prepared hollow fiber has a unique hollow structure, so that air is easily stored in the hollow structure, and a certain warm keeping effect is achieved; a certain groove structure is formed in the surface of the fiber, so that the fiber has a capillary effect and a good warm-keeping effect; the hollow fibers not only can quickly absorb moisture through the damaged outer wall, but also can facilitate moisture volatilization by virtue of the air permeability of the hollow fibers, so that the fabric can be quickly kept dry and comfortable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hollow fiber preparation technology, and in particular to a preparation process of a hollow fiber fabric with heat preservation, drying and moisture absorption functions. Background Art

[0002] In recent years, with the improvement of people's living standards, people have higher and higher requirements for the performance of clothing beyond the basic function of wearing. Usually, the basic function of fabrics is to cover shame and keep out the cold, which is also a basic need of life. However, on the basis of meeting basic material conditions, people's demand for the safety, protection, comfort, functionality and environmental protection of clothing fabrics is increasing.

[0003] The thermal insulation and moisture absorption properties of fabrics have a very important impact on the comfort of fabrics. Therefore, thermal insulation and moisture absorption properties have become part of the most important performance requirements of people for clothing.

[0004] Regarding the high-density fabrics and coated fabrics that are currently used to solve the functions of warmth retention and moisture absorption, specifically: high-density fabrics have good moisture permeability due to the large pores between the yarns in the fabric, but poor waterproofness; coated fabrics generally use a non-porous membrane coating structure, which leads to good waterproofness, but poor moisture permeability. At the same time, there is also a mainstream fabric product, namely laminated fabrics. Compared with high-density fabrics and coated fabrics, this fabric has relatively excellent comprehensive performance. This is because the core functional layer of the fabric plays a major role - the waterproof and breathable membrane. The waterproof and breathable functional membranes currently available on the market mainly include polytetrafluoroethylene hydrophobic microporous membranes and thermoplastic polyurethane hydrophilic non-porous membranes. Although the PTFE microporous membrane has excellent waterproof and breathable properties, it still has problems such as high price and unstable product quality. At the same time, due to the slippery and non-sticky nature of the PTFE polymer, its later composite process is difficult, which limits its application field.

[0005] At present, there are many cases of moisture absorption and perspiration shaped fiber applications at home and abroad. Among them, the fiber cross-section is Y-shaped, cross-shaped, M-shaped and other shaped cross-sections can obtain a certain groove structure, so that the fiber has a capillary effect and has the function of perspiration. However, the fiber still does not have air permeability and perspiration. Although the hollow fiber with a hollowness greater than 20% has a certain air permeability and perspiration permeability, due to the lack of capillary grooves, the moisture absorption, dryness and warmth retention are not ideal. Summary of the invention

[0006] The purpose of the present invention is to provide a preparation process of a hollow fiber fabric with heat preservation, dryness and moisture absorption functions. The hollow fiber fabric prepared by this process can improve the shortcomings of current fabrics in terms of warmth preservation and moisture absorption.

[0007] Specifically, the present invention adopts the following technical solutions: A preparation process of a hollow fiber fabric with heat preservation, dryness and moisture absorption function, specifically comprising the following steps: Step (1), first, selecting polyester, polylactic acid and polyester masterbatch as spinning raw materials, melt-mixing them, and hollow melt spinning using a hollow fiber spinning plate to obtain hollow fibers; the percentage of polylactic acid to polyester is 3-6%, and the percentage of polyester masterbatch to polyester is 5-10%; The polyester masterbatch comprises, by weight: 100 parts of polyester, 10-20 parts of polylactic acid, 5-10 parts of nano-barium sulfate, 3-7 parts of nano-sodium sulfate, 0.3-0.5 parts of nano-titanium dioxide, and 3-6 parts of nano-zinc oxide; the polylactic acid in the masterbatch is calculated separately from the above-mentioned polylactic acid; Step (2), making the hollow fibers obtained by spinning into yarns, washing them with water or alkali, and then weaving them to obtain hollow fiber fabrics; Step (3), subjecting the hollow fiber fabric to an impregnation modification treatment using a modified finishing liquid to obtain a hollow fiber fabric with heat-insulating, dry, and moisture-absorbing functions.

[0008] The invention adds some additives into the master batch to modify the hygroscopic property of the polyester by the additives, and utilizes the subsequent water washing and alkali washing processes to destroy the integrity of the hollow fiber, so that the hollow fiber can have better water absorption and water storage performance, and improves the hygroscopicity of the fiber fabric.

[0009] Polylactic acid can not only improve the overall biodegradability, but more importantly, it can improve the precipitation performance of various nano-additives in the masterbatch, so that the overall integrity of the fiber can be destroyed by cleaning and removing the additives during the alkaline process, thereby making the hollow inside of the fiber connected to the outside world and improving the moisture absorption effect of the fiber.

[0010] Preferably, the particle size of the nanocompound in the polyester masterbatch is 20-80 nm.

[0011] Preferably, the nano-barium sulfate, nano-sodium sulfate, nano-titanium dioxide and nano-zinc oxide in the polyester masterbatch in step (1) are first subjected to a modification treatment; the modification process is specifically as follows: the nano-powder is first dispersed in anhydrous ethanol, heated to 60° C., the pH is adjusted to 5-5.5, and then stirred for reaction for 3-5 hours, a silane coupling agent is added thereto, and the reaction is continued for another 2-5 hours; and modified nano-particles are obtained; The modified nanoparticles are placed in a maleic anhydride aqueous solution, heated to 65-70° C. for reaction for 1-2 hours, and then 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is added and the reaction is continued for 2-3 hours to obtain further modified nanoparticles.

[0012] Maleic anhydride is used to increase the carboxyl groups on the surface of the nanoparticles, which is beneficial for the nanoparticles to combine with the polyester and the basic components in the masterbatch. 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is usually used as a carboxyl activator. Here, as a preferred method, the weight percentage of the nanopowder added to the anhydrous ethanol is 5-20%, and the weight percentage of the silane coupling agent added to the anhydrous ethanol is 2-5%.

[0013] Preferably, the weight percentage content of maleic anhydride in the maleic anhydride aqueous solution is 10-15%, and the weight percentage added amount of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is 3-5%.

[0014] Preferably, the modified finishing liquid in step (3) is prepared by the following method: (1) Add 3-5 g of mesoporous silica nanoparticles to 100 ml of anhydrous ethanol, then add 5-8 ml of γ-aminopropyltriethoxysilane, stir and reflux at 50-60 ° C for 1-2 h, filter the mixture and wash the mesoporous silica nanoparticles with ethanol and water; (2) Then, the product of step (1) obtained above is placed in an aqueous solution of maleic anhydride with a mass fraction of 3-8%, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is added to react for 1-3 hours; (3) Then 0.5-1g of the above product is placed in 100ml of anhydrous ethanol, and 1-3% of silver nitrate is added thereto, and the mixture is stirred for reaction for 3-8h; the obtained mixed solution is filtered and washed with ethanol and water respectively; then the obtained product is placed in 100ml of anhydrous ethanol solution again, 3-8ml of 0.01mol / L ascorbic acid solution is added, and the reaction is carried out for 1-2h, and then 1-3ml of 0.1mol / L sodium citrate aqueous solution is added to react for 1-2h; finally, the mixture is filtered and washed; and a modified finishing agent is obtained; (4) Prepare a 3-10% aqueous solution of the modified finishing agent to obtain a modified finishing liquid.

[0015] Through modification, the fabric can be modified and finished to be antibacterial. Specifically, nanosilver is loaded on mesoporous silica nanoparticles to achieve an antibacterial effect on the fabric.

[0016] Preferably, in step (2), the mass ratio of the product of step (1) to maleic anhydride and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is 100:(50-80):(10-30).

[0017] A fabric prepared by the process.

[0018] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses polyester and a small amount of polylactic acid to blend and then weave to obtain hollow fibers. Polyester masterbatch is added to the hollow fibers at the same time. By utilizing the addition of the masterbatch and the effect of polylactic acid, the fiber wall of the hollow fibers can be damaged through subsequent water washing and alkali washing processes, which is beneficial to absorb water, thereby improving the moisture absorption effect. The prepared hollow fiber itself has a unique hollow structure, which makes it easy to store air in the hollow structure and has a certain warming effect; the certain groove structure on the fiber surface gives the fiber a capillary effect, which has a good warming effect; the hollow fiber can not only quickly absorb moisture through the damaged outer wall, but also use its air permeability to help the volatilization of moisture, so as to quickly keep the fabric dry. DETAILED DESCRIPTION

[0019] Representative embodiments will now be further refined. It should be understood that the following description is not intended to limit the embodiments to a preferred embodiment. On the contrary, it is intended to cover alternatives, modifications and equivalents that may be included in the essence and scope of the embodiments defined by the appended claims.

[0020] The applicant provides a preparation process of a hollow fiber fabric with heat preservation, dryness and moisture absorption functions.

[0021] Specifically, the preparation process comprises the following steps: Step (1), first, selecting polyester, polylactic acid and polyester masterbatch as spinning raw materials, melt-mixing them, and hollow melt spinning using a hollow fiber spinning plate to obtain hollow fibers; the percentage of polylactic acid to polyester is 3-6%, and the percentage of polyester masterbatch to polyester is 5-10%; The polyester masterbatch comprises, by weight: 100 parts of polyester, 10-20 parts of polylactic acid, 5-10 parts of nano-barium sulfate, 3-7 parts of nano-sodium sulfate, 0.3-0.5 parts of nano-titanium dioxide, and 3-6 parts of nano-zinc oxide; the particle size of the nano-compound is 20-80nm; Step (2), making the hollow fibers obtained by spinning into yarns, washing them with water or alkali, and then weaving them to obtain hollow fiber fabrics; Step (3), subjecting the hollow fiber fabric to an impregnation modification treatment using a modified finishing liquid to obtain a hollow fiber fabric with heat-insulating, dry, and moisture-absorbing functions.

[0022] Regarding the above steps, which involve the modification of the masterbatch and the preparation of the modified finishing liquid, the masterbatch and the modified finishing liquid are prepared according to the following method.

[0023] First, regarding step (1), the nano-barium sulfate, nano-sodium sulfate, nano-titanium dioxide, and nano-zinc oxide in the polyester masterbatch in step (1) are first modified; the modification process is as follows: The nano powder is first dispersed in anhydrous ethanol, heated to 60°C, and the pH is adjusted to 5-5.5. The weight percentage of the nano powder added to the anhydrous ethanol is 5-20%. Then, the mixture was stirred and reacted for 3-5 hours, and a silane coupling agent was added thereto, wherein the weight percentage of the silane coupling agent added to the anhydrous ethanol was 2-5%, and the mixture was reacted for another 2-5 hours to obtain modified nanoparticles; The modified nanoparticles are placed in a maleic anhydride aqueous solution, heated to 65-70°C for reaction for 1-2 hours, and then 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is added and the reaction is continued for 2-3 hours to obtain further modified nanoparticles. The weight percentage content of maleic anhydride in the maleic anhydride aqueous solution is 10-15%, and the weight percentage addition amount of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is 3-5%.

[0024] The purpose of the above method is to improve the dispersibility of each component in polyester by modifying its properties, and to modify the properties of polyester by various fillers.

[0025] Regarding the modified finishing liquid used, the modified finishing liquid is prepared by the following method: (1) Add 3-5 g of mesoporous silica nanoparticles to 100 ml of anhydrous ethanol, then add 5-8 ml of γ-aminopropyltriethoxysilane, stir and reflux at 50-60 ° C for 1-2 h, filter the mixture and wash the mesoporous silica nanoparticles with ethanol and water; (2) Then, the product of step (1) obtained above is placed in an aqueous solution of maleic anhydride with a mass fraction of 3-8%, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is added to react for 1-3 hours; the mass ratio of the product of step (1) to maleic anhydride and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is 100:(50-80):(10-30); (3) Then 0.5-1g of the above product is placed in 100ml of anhydrous ethanol, and 1-3% of silver nitrate is added thereto, and the mixture is stirred for reaction for 3-8h; the obtained mixed solution is filtered and washed with ethanol and water respectively; then the obtained product is placed in 100ml of anhydrous ethanol solution again, 3-8ml of 0.01mol / L ascorbic acid solution is added, and the reaction is carried out for 1-2h, and then 1-3ml of 0.1mol / L sodium citrate aqueous solution is added to react for 1-2h; finally, the mixture is filtered and washed; and a modified finishing agent is obtained; (4) Prepare a 3-10% aqueous solution of the modified finishing agent to obtain a modified finishing liquid.

[0026] Embodiment 1: The applicant prepared a hollow fiber fabric with heat preservation, dryness and moisture absorption functions, and the specific process includes: preparing modified nanoparticles; preparing a modified finishing liquid; Spinning and weaving to obtain fabrics; and finishing the fabrics.

[0027] The details are as follows: First, the modified nanoparticles were prepared; The modified nanoparticles were prepared as follows: The nano powders of barium sulfate, nano sodium sulfate, nano titanium dioxide and nano zinc oxide with a particle size of 20-80 nanometers are modified in the following ways: First, disperse it in anhydrous ethanol, heat it to 60°C, adjust the pH to 5.5, and add 8% by weight of nanopowder to anhydrous ethanol. Then, the mixture was stirred and reacted for 4 hours, and a silane coupling agent was added thereto, wherein the weight percentage of the silane coupling agent added to the anhydrous ethanol was 3%, and the mixture was reacted for another 3 hours to obtain modified nanoparticles; The modified nanoparticles were placed in a 12% maleic anhydride aqueous solution, heated to 65°C for reaction for 2 hours, and then 3% 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide was added and the reaction continued for 2 hours to obtain further modified nanoparticles.

[0028] Second, prepare the modified finishing liquid, which is prepared by the following method: (1) 4 g of mesoporous silica nanoparticles were added to 100 ml of anhydrous ethanol, and then 6 ml of γ-aminopropyltriethoxysilane was added thereto. The mixture was stirred and refluxed at 56 °C for 2 h. The mixed solution was filtered and the mesoporous silica nanoparticles were cleaned with ethanol and water. (2) Then, the product of step (1) obtained above is placed in an aqueous solution of maleic anhydride having a mass fraction of 5%, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is added to react for 2 hours; the mass ratio of the product of step (1) to maleic anhydride and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is 100:50:25; (3) Then 1g of the above product is placed in 100ml of anhydrous ethanol, and 1-3% silver nitrate is added thereto, and the mixture is stirred for reaction for 4h; the obtained mixed solution is filtered and washed with ethanol and water respectively; then the obtained product is placed in 100ml of anhydrous ethanol solution again, 5ml of 0.01mol / L ascorbic acid solution is added and reacted for 1h, and then 2ml of 0.1mol / L sodium citrate aqueous solution is added and reacted for 2h; finally, the mixture is filtered and washed; and a modified finishing agent is obtained; (4) Prepare a 5% aqueous solution of the modifying finishing agent to obtain the modifying finishing liquid.

[0029] Third, the yarn is spun and woven, and then finished.

[0030] Step (1), first, selecting polyester, polylactic acid and polyester masterbatch as spinning raw materials, melt-mixing them, and hollow melt spinning using a hollow fiber spinning plate to obtain hollow fibers; the percentage of polylactic acid to polyester is 4%, and the percentage of polyester masterbatch to polyester is 6%; The polyester masterbatch comprises, by weight: 100 parts of polyester, 12 parts of polylactic acid, 6 parts of nano-barium sulfate, 5 parts of nano-sodium sulfate, 0.4 parts of nano-titanium dioxide, and 5 parts of nano-zinc oxide; Step (2), the hollow fiber obtained by spinning is made into yarn, which is washed with alkaline solution of pH 8-8.5, and then the hollow fiber fabric is obtained through weaving process; the specification of the yarn is 98D / 36F Step (3), subjecting the hollow fiber fabric to an impregnation modification treatment using a modified finishing liquid to obtain a hollow fiber fabric with heat-insulating, dry, and moisture-absorbing functions.

[0031] Embodiment 2: The applicant prepared a hollow fiber fabric with heat preservation, dryness and moisture absorption functions, and the specific process includes: preparing modified nanoparticles; preparing a modified finishing liquid; Spinning and weaving to obtain fabrics; and finishing the fabrics.

[0032] The modified nanoparticles and the modified finishing liquid were prepared in the same manner as in Example 1.

[0033] Fabrics follow these steps: Step (1), first, selecting polyester, polylactic acid and polyester masterbatch as spinning raw materials, melt-mixing them, and hollow melt spinning using a hollow fiber spinning plate to obtain hollow fibers; the percentage of polylactic acid to polyester is 6%, and the percentage of polyester masterbatch to polyester is 8%; The polyester masterbatch comprises, by weight: 100 parts of polyester, 10 parts of polylactic acid, 6 parts of nano-barium sulfate, 3 parts of nano-sodium sulfate, 0.5 parts of nano-titanium dioxide, and 6 parts of nano-zinc oxide; Step (2), the hollow fiber obtained by spinning is made into yarn, which is washed with alkaline solution of pH 8-8.5, and then the hollow fiber fabric is obtained through weaving process; the specification of the yarn is 98D / 36F Step (3), subjecting the hollow fiber fabric to an impregnation modification treatment using a modified finishing liquid to obtain a hollow fiber fabric with heat-insulating, dry, and moisture-absorbing functions.

[0034] Comparative Example 1: Ordinary polyester fiber is used to prepare hollow fiber fabric; the specification of the yarn is 98D / 36F.

[0035] The fabrics of Example 1, Example 2 and Comparative Example 1 were tested for moisture absorption performance. The moisture absorption performance test was conducted on the samples in accordance with the national standard GB / T 21655.1-2008 "Evaluation of moisture absorption and quick-drying properties of textiles Part 1: Single combination test method". The performance test results are as follows: Example 1 Example 2 Comparative Example 1 Water absorption / % 375 368 283 Droplet diffusion time / s 1.7 1.8 2.6 From the data in the above table, it can be seen that the water absorption of the hollow fiber fabric of the present invention is better, while the water absorption of the hollow fiber fabric in the comparative example is poor.

[0036] The fabrics of Example 1, Example 2 and Comparative Example 1 were tested for antibacterial performance. The antibacterial performance test was conducted in accordance with the national standard GB / T 20944.2-2007 "Evaluation of Antibacterial Performance of Textiles Part 2: Absorption Method", and Escherichia coli and Staphylococcus aureus were used for the antibacterial performance test. The antibacterial performance is shown in the following table: Antibacterial rate / % Example 1 Example 2 Comparative Example 1 Escherichia coli 95.3 93.8 68.2 staphylococcus 93.5 94.2 70.9 It can be seen from the above test results that the fabric prepared by the present invention has a certain antibacterial effect.

[0037] After washing the fabric 5 times, the antibacterial effect can still maintain more than 95% of the original antibacterial effect.

[0038] The thermal insulation performance of the fabrics of Example 1, Example 2 and Comparative Example 1 was tested in accordance with the national standard GB / T 11048. Among them, thermal insulation rate, heat transfer coefficient, thermal resistance value, Crowe value, etc. are important parameters for measuring the thermal insulation effect of fabrics.

[0039] Insulation rate (%) = (starting temperature - ending temperature) / starting temperature × 100%.

[0040] Under the same environment, the experimental temperature is 20℃ ± 2°; under the environment of relative humidity of 65%, the insulation rate is shown in the following table: Example 1 Example 2 Comparative Example 1 Insulation rate 76% 68% 52% Thermal conductivity 3.4 3.9 6.5 From the above data, it can be seen that the fabric product of the present invention has a considerable heat preservation effect.

[0041] It is obvious to those skilled in the art that certain modifications, combinations and variations can be made based on the above teachings.

Claims

1. A preparation process of a hollow fiber fabric with heat preservation, dryness and moisture absorption function, characterized by: The specific steps include: Step (1), first, selecting polyester, polylactic acid and polyester masterbatch as spinning raw materials, melt-mixing them, and hollow melt spinning using a hollow fiber spinning plate to obtain hollow fibers; the percentage of polylactic acid to polyester is 3-6%, and the percentage of polyester masterbatch to polyester is 5-10%; The polyester masterbatch comprises, by weight: 100 parts of polyester, 10-20 parts of polylactic acid, 5-10 parts of nano-barium sulfate, 3-7 parts of nano-sodium sulfate, 0.3-0.5 parts of nano-titanium dioxide, and 3-6 parts of nano-zinc oxide; Step (2), making the hollow fibers obtained by spinning into yarns, washing them with water or alkali, and then weaving them to obtain hollow fiber fabrics; Step (3), subjecting the hollow fiber fabric to an impregnation modification treatment using a modified finishing liquid to obtain a hollow fiber fabric with heat-insulating, dry, and moisture-absorbing functions.

2. The preparation process of the hollow fiber fabric with heat preservation, dryness and moisture absorption function according to claim 1, characterized in that: The particle size of the nanocompound in the polyester masterbatch is 20-80nm.

3. The preparation process of the hollow fiber fabric with heat preservation, dryness and moisture absorption function according to claim 1, characterized in that: In step (1), the nano-barium sulfate, nano-sodium sulfate, nano-titanium dioxide and nano-zinc oxide in the polyester masterbatch are first subjected to a modification treatment; the modification process is specifically as follows: the nano-powder is first dispersed in anhydrous ethanol, heated to 60° C., the pH is adjusted to 5-5.5, and then stirred for reaction for 3-5 hours, a silane coupling agent is added thereto, and the reaction is continued for another 2-5 hours; and modified nano-particles are obtained; The modified nanoparticles are placed in a maleic anhydride aqueous solution, heated to 65-70° C. for reaction for 1-2 hours, and then 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is added and the reaction is continued for 2-3 hours to obtain further modified nanoparticles.

4. The process for preparing the hollow fiber fabric with heat preservation, dryness and moisture absorption function according to claim 3, characterized in that: The weight percentage of the nano powder added to the anhydrous ethanol is 5-20%, and the weight percentage of the silane coupling agent added to the anhydrous ethanol is 2-5%.

5. The process for preparing the hollow fiber fabric with heat preservation, dryness and moisture absorption function according to claim 3, characterized in that: The weight percentage content of maleic anhydride in the maleic anhydride aqueous solution is 10-15%, and the weight percentage added amount of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is 3-5%.

6. The process for preparing the hollow fiber fabric with heat preservation, dryness and moisture absorption function according to claim 1, characterized in that: The modified finishing liquid in step (3) is prepared by the following method: (1) Add 3-5 g of mesoporous silica nanoparticles to 100 ml of anhydrous ethanol, then add 5-8 ml of γ-aminopropyltriethoxysilane, stir and reflux at 50-60 ° C for 1-2 h, filter the mixture and wash the mesoporous silica nanoparticles with ethanol and water; (2) Then, the product of step (1) obtained above is placed in an aqueous solution of maleic anhydride with a mass fraction of 3-8%, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is added to react for 1-3 hours; (3) Then 0.5-1g of the above product is placed in 100ml of anhydrous ethanol, and 1-3% of silver nitrate is added thereto, and the mixture is stirred for reaction for 3-8h; the obtained mixed solution is filtered and washed with ethanol and water respectively; then the obtained product is placed in 100ml of anhydrous ethanol solution again, 3-8ml of 0.01mol / L ascorbic acid solution is added, and the reaction is carried out for 1-2h, and then 1-3ml of 0.1mol / L sodium citrate aqueous solution is added to react for 1-2h; finally, the mixture is filtered and washed; and a modified finishing agent is obtained; (4) Prepare a 3-10% aqueous solution of the modified finishing agent to obtain a modified finishing liquid.

7. The process for preparing the hollow fiber fabric with heat preservation, dryness and moisture absorption function according to claim 6, characterized in that: The mass ratio of the product of step (1) to maleic anhydride and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide in step (2) is 100:(50-80):(10-30).

Citation Information

Cited By

  • Rapid moisture-conducting fiber as well as preparation method and application thereof

    CN119685965A

  • Gluing process for manufacturing cool fabric

    CN119932932A